2013
DOI: 10.1002/cam4.142
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of toxicity and outcomes of concurrent radiotherapy with carboplatin/paclitaxel or cisplatin/etoposide in stage III non–small cell lung cancer

Abstract: Concurrent chemoradiotherapy (CCRT) has become the standard of care for patients with unresectable stage III non–small cell lung cancer (NSCLC). The comparative merits of two widely used regimens: carboplatin/paclitaxel (PC) and cisplatin/etoposide (PE), each with concurrent radiotherapy, remain largely undefined. Records for consecutive patients with stage III NSCLC treated with PC or PE and ≥60 Gy chest radiotherapy between 2000 and 2011 were reviewed for outcomes and toxicity. Survival was estimated using t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 34 publications
3
21
1
Order By: Relevance
“…[22] The incidence of severe neutropenia and thrombocytopenia was considerably lower in our study (12% and 0%, respectively) compared with other studies including PE regimen (39% vs. 10%). [22] Variations in terms of efficiency and toxicity have been reported between different nations receiving the same CT regimens. [37] These differences mainly emerge from ethnic instabilities in single-nucleotide polymorphism distributions that affect CT transport and metabolism.…”
Section: Discussioncontrasting
confidence: 48%
See 1 more Smart Citation
“…[22] The incidence of severe neutropenia and thrombocytopenia was considerably lower in our study (12% and 0%, respectively) compared with other studies including PE regimen (39% vs. 10%). [22] Variations in terms of efficiency and toxicity have been reported between different nations receiving the same CT regimens. [37] These differences mainly emerge from ethnic instabilities in single-nucleotide polymorphism distributions that affect CT transport and metabolism.…”
Section: Discussioncontrasting
confidence: 48%
“…[19] Several recent studies compared PE with PC in terms of efficiency and produced conflicting results. [14,2022] However, docetaxel is a third-generation CT agent and its effectiveness has been demonstrated in many studies indicating that the docetaxel-cisplatin (DP) regimen was equal or superior to a PV combination. [2326] In addition, docetaxel proved its superiority to vinca-alkaloids in combinations in both metastatic and LA-NSCLC.…”
Section: Introductionmentioning
confidence: 99%
“…Liew et al . demonstrated that a taxane‐contained regimen of concurrent chemotherapy could lead to serious radiation pneumonitis in non‐small cell lung cancer patients . This phenomenon suggests that a TP regimen must be used with caution in cases of concurrent radiochemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Patient comorbidities may help guide the choice of agent. While overall survival seems to be similar with these, less haematological toxicity but a higher risk of radiation pneumonitis was observed with Carbo/paclitaxel when compared to Cis/Eto [41]. Pemetrexed (Pem)/Cis seems to have a survival benefit for patients with metastatic non-squamous NSCLC [42]; however, no clear advantages are reported in locally advanced disease.…”
Section: Radiochemotherapymentioning
confidence: 98%